(3EaTGA GdSQ GdeUhf ef VejQ JUMjM GHf bGVi YLdhfs - (3eMeO Hf CMeO Hf eMeO GdehUdj GdMfHdj, CHh YHO Gddg, GdeYQha HTYdI, hjbGd dg GHf GdehbY,J (B656 (3g` s ((3Ydi GdMSfi GdTGaYi Ke GdYLdhfi s)
(3ChdgG (B:s
(3cJGH jUM ef cJGH GdaQGFV hGdeQGO HgG QSGFd bSeI GdehGQjK s
(3BNQgG (B:s
(3GdEeSGc Yf Pdc deQV fGRdJi Je s
(3GdfSNI HgG MhGTs
(3HBNQg aGFOgs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B321 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B315s
Keywords: (3Gdabg GdTGaYjs